Impact Of Disciplinary Work And Incentives On The Work Of Honourable Employees In The Eastern Globe Local Police Office - Sugiono Sugiono; Dede Dede; Hikmatul Aliyah; Ani Hasya Utari (Utan Kayu Publishing, 2024)
Improving staff performance has been a major focus for organizations in various sectors and industries. In an era of globalization and increasingly complex competition, organizations need to optimize their human resource potential to their strategic goals. Implementing good work discipline can improve the productivity and quality of work of employees, while giving incentives is identified as a factor that can motivate employees to more optimum work outcomes.The author formulates the following question: 1.Does work discipline influence on the performance of Honourable Officers in the East Lampung Regional Revenue Agency Office? 2.Does the incentive affect on the Performance of Honorable Officials in the Eastern Lampung District Revenues Office?3. Do Work Discipline and Incentives Influence on the Performance of Honourable Officers in the East Lampung Regional Revenue Agency Office? The data collection techniques in this study are interviews and questionnaires. The population in this study is the entire staff of the East Lampung Regional Revenue Agency office of 50 people. Samples are taken using saturation/sensus sampling. Data analysis techniques using double linear regression formulas with the help of SPSS 26 applications. The results of this study show that (1) employee performance is influenced by the Working Discipline and incentive variable of 44.9% and the rest is affected by other variables (2) Working discipline has a positive impact on employee's performance (3) incentives have a positive effect on staff performance (4) Disciplinary incentivity has positive and significant impact on employees' performance.